1999
DOI: 10.1088/0953-2048/12/11/359
|View full text |Cite
|
Sign up to set email alerts
|

A new epitaxial BaSnO3buffer layer for YBa2Cu3O7-deltathin films on MgO substrates

Abstract: 45° grain boundaries, which drastically increase surface resistance (RS) in superconducting YBa2Cu3O7- films for microwave devices on MgO substrates, are eliminated using a new buffer layer of BaSnO3.BaSnO3 buffer layers and YBa2Cu3O7- films are grown by ArF pulsed laser deposition. Epitaxial relationships among BaSnO3, YBa2Cu3O7- and MgO are confirmed by x-ray -scanning. The RS values of the YBa2Cu3O7- films are measured using a dielectric resonator with 22 GHz TE011 mode. The epitaxial YBa2Cu3O7- films grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Even so, the required energies per pulse are fairly high and most readily achieved with excimer lasers [39]. Lasers using KrF excimers (248 nm, typically 20-35 ns pulse duration) have been used most often in PLD, but successful film growth has also been achieved using ArF (193 nm) [40][41][42] and XeCl (308 nm) [43][44][45][46][47] excimers.…”
Section: Ablation and Plasma Formationmentioning
confidence: 99%
“…Even so, the required energies per pulse are fairly high and most readily achieved with excimer lasers [39]. Lasers using KrF excimers (248 nm, typically 20-35 ns pulse duration) have been used most often in PLD, but successful film growth has also been achieved using ArF (193 nm) [40][41][42] and XeCl (308 nm) [43][44][45][46][47] excimers.…”
Section: Ablation and Plasma Formationmentioning
confidence: 99%
“…BaSnO 3 with a cubic perovskite crystal type structure (a = 4.12 Å) has been investigated as a buffer layer on MgO substrates for growing smoother YBCO films for microwave applications [13]. Although BaSnO 3 has been studied for flux pinning enhancements in melt processed YBCO [14,15], here we provide an initial demonstration of effectively incorporating BaSnO 3 nanoparticles as pinning material in YBCO films.…”
Section: Introductionmentioning
confidence: 98%
“…But it is reported that for the 123 films deposited on MgO, there exists an inter layer of barium salt at the interface if the temperature of processing is above 700 • C [10]. Also another problem reported with the films grown on MgO is the presence of 45 • in-plane misaligned grains [11,12], which used to degrade the microwave properties of the 123 superconductor films grown on MgO substrates [13]. One solution to these problems is to use a suitable buffer layer over MgO substrate for the growth of 123 superconductor films.…”
Section: Introductionmentioning
confidence: 99%